2014
DOI: 10.1159/000371871
|View full text |Cite
|
Sign up to set email alerts
|

β-Blocker Use and Risk of Recurrence in Patients with Early Breast Cancer

Abstract: Aim: We evaluated whether the concurrent β-blocker use in early breast cancer patients influenced the outcome in terms of preventing tumor recurrence after adjuvant chemotherapy. Methods: We retrospectively reviewed the medical records of 610 patients with breast cancer. Thereafter, we compared overall disease-free survival (DFS) between β-blocker users and nonusers. Results: Those not receiving β-blockers had a relatively longer mean DFS (10.8 vs. 9.7 years), although the difference did not reach statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 3 publications
1
27
0
Order By: Relevance
“…Our results are in line with preclinical in vitro and in vivo studies, showing the antiangiogenetic and antimetastatic property of BB, in particular propranolol . Beside preclinical studies, a significant reduction in BC specific mortality and recurrence was observed in some previous observational studies, while others did not confirm these results …”
Section: Discussionsupporting
confidence: 88%
“…Our results are in line with preclinical in vitro and in vivo studies, showing the antiangiogenetic and antimetastatic property of BB, in particular propranolol . Beside preclinical studies, a significant reduction in BC specific mortality and recurrence was observed in some previous observational studies, while others did not confirm these results …”
Section: Discussionsupporting
confidence: 88%
“…No significant association was found between β-blocker use and mortality of breast cancer patients in six studies (Ganz et al, 2011;Sendur et al, 2012;Cardwell et al, 2013;Holmes et al, 2013aHolmes et al, , 2013bSakellakis et al, 2015), two of which, nevertheless, reported a nonstatistically significant decreased risk of breast cancer death (Ganz et al, 2011;Holmes et al, 2013a). Melhem-Bertrandt et al (2011) showed that overall survival of breast cancer patients was not affected by β blockers, but relapse-free survival was significantly improved, especially in triple-negative breast cancer patients.…”
Section: Discussionmentioning
confidence: 97%
“…Ten studies have investigated the effect of β-blocker use on the survival of breast cancer patients (Powe et al, 2010;Barron et al, 2011;Ganz et al, 2011;Melhem-Bertrandt et al, 2011;Sendur et al, 2012;Botteri et al, 2013;Cardwell et al, 2013;Holmes et al, 2013aHolmes et al, , 2013bSakellakis et al, 2015). No significant association was found between β-blocker use and mortality of breast cancer patients in six studies (Ganz et al, 2011;Sendur et al, 2012;Cardwell et al, 2013;Holmes et al, 2013aHolmes et al, , 2013bSakellakis et al, 2015), two of which, nevertheless, reported a nonstatistically significant decreased risk of breast cancer death (Ganz et al, 2011;Holmes et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to evaluate β-blockers (BB) since previous studies evaluated the effect of BB on mortality in cancer patients in general and in breast cancer patients specifically, but their findings were inconclusive [23,26,27,28,29,30]. …”
Section: Methodsmentioning
confidence: 99%